A nova (des)ordem internacional: refugiados, globalização e direitos humanos. - Silva, Bruno de Lima (Universidade do Vale do Rio dos Sinos, 2023)
The theme of this The theme of this dissertation is migrations, refugees and human rights in global society. The current society is formed by a tangle of cogent relationships, these relationships make the world more complex and multifaceted. In this scenario, contemporary migrations have several consequences, sometimes thousands of individuals are stripped of their identity, leaving only the status of refugee, that is, without a place, without a State. In this way, the general objective of the research is to analyze the effective protection that refugees currently receive from the Nation-States, analyzing the systems of Law and Politics. Therefore, the dissertation is justified by the topicality, breadth and complexity of the proposed theme. In this context, the central problem of the research is how are the systems of Law and Politics responding to the demands of contemporary migratory movements, especially with regard to Human Rights and the effective protection of refugees in global society? In this sense, the dissertation presents the hypothesis that currently the forms of protection offered by the Nation States are inefficient to guarantee an effective refugee. Thus, these people suffer from various human rights violations, requiring a change in the way this situation is treated by the international community. To change this scenario, legal, political and institutional changes are necessary. To carry out this analysis, Niklas Luhmann's theory of autopoietic systems proves to be a sophisticated way of observing the complexity of society, as well as the use of the pragmatic-systemic matrix for legal observation. Thus, the research has a descriptive and qualitative nature, having as an epistemological basis the systemic-constructivist methodology, in which reality is constructed through an observer. As for research techniques, bibliographic review of national and foreign doctrine, indirect documentation, qualitative analysis of court decisions and the use of jurimetry will be used. In final aspects, some possibilities are pointed out to follow paths, in order to equate the demands regarding the theme of refugees, as well as, to avoid the constant violations of Human Rights that this category has been facing.
Keywords: Direitos Humanos; Direito; Migrações; Política; Refugiados; Human Rights; Rights; Migrations; Policy; Refugees; ACCNPQ::Ciências Sociais Aplicadas::Direito